Aistear: the Early Childhood Curriculum Framework Understanding its Place in Junior and Senior Infant Classrooms in 2021 and Beyond. - Healy, Sadhbh (Marino Institute of Education, 2021)
This study seeks to understand the perspectives of teachers on the Aistear framework for early years learning in Junior and Senior Infant classrooms of 2021, and considers the relevance of this framework in classrooms in the future. Despite the many benefits associated with this early childhood curriculum, recent studies revealed gaps in the framework, particularly in relation to its implementation. This quantitative study adopted a survey method of online questionnaires to uncover if the perspectives of infant teachers in 2021 of the Aistear framework were in line with current published literature. This study revealed that Aistear does hold a place in Junior and Senior Infant classrooms of 2021 and there is a future for this framework in these classrooms. There was also widespread recognition that more support is needed and improvements made to the current set up. It was identified that infant teachers today had a greater appreciation of Aistear than the current literature suggests. The researcher identified that ITE and the emphasis it puts on play-based learning and Aistear in recent years, is having a positive impact on Newly Qualified Teachers (NQTs) as it appears they are implementing the Aistear framework in their classrooms upon finishing their degrees. This could also explain why respondents indicated a relatively high level of confidence when it comes to the implementation of Aistear and their role as teacher. However, issues identified by respondents relating to Aistear concur with recent studies. In order to overcome these challenges and improve the implementation of this framework in primary infant classes, the researcher recommends that; teacher training is provided for all infant teachers who wish to avail of it, Aistear is made compulsory for all infant classes, additional funding and resources are made available to support schools and teachers provide a suitable, stimulating learning environment for children during Aistear and finally, Aistear will be subject to inspection as part of a Whole School Evaluation (WSE).
Keywords: Aistear; Early years learning; Curriculum; Newly Qualified Teachers (NQTs); Whole School Evaluation (WSE).; Primary education; Education; Teachers; Early Childhood Education; Curriculum planning